Образ Іверської Божої Матері в українській бароковій літературі - Матушек, Олена; Matushek, Olena (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті розглянуто літературний образ ікони Іверської Богородиці на матеріалі «Неба нового» Іоаникія Галятовського. Проаналізувавши оповідання, ми прийшли до висновку, що основними функціями образу Іверської Божої Матері є апостольська та функція захисниці й заступниці Іверського монастиря. This article considers the literary image of the icon of the Iberian Mother of God in the book «New Heaven» written the author of the XVII-th century Ioanykiy Galyatovs’kiy. After analyzing the miracle-stories we came to the conclusion that the main functions of the Mother of God are apostolic and patron-protector of Iberian monastery on the Mount Athos. The first is realized through the motives of the Descent of the Holy Spirit; obtaining (by lot) the Mount Athos as a ground for Christian preaching by Virgin, her traveling to the Mount Athos, preaching to the Gentiles, converting them to Christianity. The second function is represented by the motives of protection the monastery from sinners and impure in heart people, barbaric attacks. In addition, the Mother of God appears as a guardian of monks when she filled the granaries of the monastery with grain, and the vessels – wine and olive.
The Image of the Iberian Mother of God in Ukrainian Baroque Literature
Keywords: Афон; Іверська ікона Богородиці (Портаїтиса); бароко; оповідання-міраклі; функції дійових осіб; Athos; Iberian icon of the Virgin (Portaitissa); Baroque; miracle stories; features actors